Cannabis sativa L. Bioactive Compounds and Their Protective Role in Oxidative Stress and Inflammation - Kopustinskiene, Dalia M; Masteikova, Ruta; Lazauskas, Robertas; Bernatoniene, Jurga (Antioxidants, 2022)
Cannabis (Cannabis sativa L.) plants from the family Cannabidaceae have been used since ancient times, to produce fibers, oil, and for medicinal purposes. Psychoactive delta-9-tetrahydrocannabinol (THC) and nonpsychoactive cannabidiol (CBD) are the main pharmacologically active compounds of Cannabis sativa. These compounds have, for a long time, been under extensive investigation, and their potent antioxidant and inflammatory properties have been reported, although the detailed mechanisms of their actions have not been fully clarified. CB1 receptors are suggested to be responsible for the analgesic effect of THC, while CB2 receptors may account for its immunomodulatory properties. Unlike THC, CBD has a very low affinity for both CB1 and CB2 receptors, and behaves as their negative allosteric modulator. CBD activity, as a CB2 receptor inverse agonist, could be important for CBD anti-inflammatory properties. In this review, we discuss the chemical properties and bioavailability of THC and CBD, their main mechanisms of action, and their role in oxidative stress and inflammation.